I hate to leave this beautiful place - Norman, Howard A. (Houghton Mifflin Harcourt, 2013)
A memoir details the haunting and redemptive events of the author's life, covering such topics as his con-man father's betrayal, the murder-suicide of a houseguest, and his decade spent in the Arctic as a translator of Inuit tales.